Rapid response redevelopment: a study of an English-to-Chinese translation course moving online - Cook Angela; Dianati Seb; Spinelli Franciele; Lai Yen-Ying (Journal of China Computer-Assisted Language Learning)
In early 2020, the tertiary sector in Australia, as in many other parts of the world, was confronted with a series of unforeseen challenges arising from the coronavirus epidemic. As governments responded to the crisis by implementing increasingly strict social distancing and isolation measures, universities had little choice but to adapt their courses for online delivery. The ensuing chaos and confusion prompted academics and support staff to adapt quickly to changing delivery while continuing to offer high-quality teaching and learning experiences. This mixed-methods study explores the approaches that were adopted in a translation course that moved fully online and examines students’ engagement with and evaluation of the new course design. The findings reveal that it is possible to maintain high levels of student satisfaction by ensuring a clearly structured course design in an online mode with interactive and engaging course materials. This has implications for university lecturers wishing to redesign courses in an online or blended format, especially under time pressure.